Design, formulation, and evaluation of curcumin-loaded nanosponges for the effective management of colitis - Praharsh Kumar Mandadhi Rajendra, Karthik Ganesan, Bala Sai Souith Nidamanuri, Jawahar Natarajan, Nirmala Puttaswamy (Journal of Applied Pharmaceutical Science, 2022)
Nanosponges are drug delivery systems consisting of nano-sized sponges incorporated with drug substances. Recently, this technology has advanced the management of many diseases which require targeted delivery. This technique can provide enhanced permeability owing to its size range. Curcumin-loaded nanosponges (CURNS) were prepared with the objective of enhancing their permeability. They were formulated by emulsion solvent diffusion method using minimum run screen design. By the initial trails, the constraints for independent variables, polymer concentration, and stirring speed were standardized and experimental runs were generated. The prepared nanosponges were characterized by scanning electron microscopy, micrometric properties, %yield, drug entrapment efficiency, in vitro release studies, in vitro release kinetics, and in vivo pharmacokinetics. According to the International Council for Harmonization of Technical Requirements for Pharmaceuticals for Human Use (ICH) norms, accelerated stability experiments for the optimized formulation were conducted. The scanning electron microscope images prove that the particles are spherical, porous on their outer surface, and spongy. The average particle size of the optimized formulation was 166.3 ± 23.32 nm, suitable for oral delivery. The optimized formulation showed controlled release of the drug with enhanced release in the colon, indicating colon-specific release. Curve-fitting analysis followed the Higuchi model. Pharmacokinetics and biodistribution results of CURNS after oral administration in rabbits proved that CURNS showed a significantly different pharmacokinetic property than that of pure curcumin solution. AUC0−t of CURNS (11.55 ± 1.123 μg/ml per minute) in plasma was around 3.07-fold greater than CUR solution (3.755 ± 0.985 μg/ml per minute), and the mean residence time (23.0118 ± 4.563 vs. 13.921 ± 5.653 hours) was 1.42-fold longer. These findings revealed that the bioavailability of curcumin was increased. Hence, nanosponges of curcumin were found to be more effective.
Keywords: Curcumin, nanosponges, colon targeting, pharmacokinetics